Optical Stimulation Luminescence Dating of Deltas Revealed the Early to Mid-Holocene Lake-level Fluctuations of Daihai, Inner Mongolia, Northern China - Huang, Shixin; Chun, Xi (Frontiers in Earth Science, 2021)
Lake level reconstruction of inland enclosed lakes especially for monsoon sensitive areas is of great significance to reveal regional climate changes. Daihai, a typical enclosed lake at the marginal of the East Asian summer monsoon (EASM) area in north China, is sensitive to climate changes because of its unique regional characteristics. There were a series of lakeshore terraces, highstand lacustrine sediments and braided river deltas, providing sufficient geomorphologic and stratigraphic evidence for the reconstruction of Daihai lake level fluctuations. Reconstructed Lake level variations during the early and mid-Holocene were constructed based on 22 quartz Optical Stimulated Luminescence (OSL) ages from six well-preserved profiles around Daihai basin. Our results indicated Daihai showed a relative low level at 10.2 ka, and gradually increasing lake level following the enhanced monsoon precipitation during the middle Holocene. Specifically, the high lake level began to develop at 8.1 ka and reached the maximum at 5.2 ka with ~40 m higher than present. At this time, the lake area expanded to ~400 km2, approximately six times as large as that of present, corresponding to the maximum monsoon precipitation and intensity of EASM during the middle Holocene. Whereas, our stratigraphic records showed a part of the depositional records in the north and east of the Daihai were missed after 5.2 ka, probably indicating a sudden drop of Daihai lake level. These rapid level fluctuations were likely to be interpreted by some local scenarios and need to further investigate in the future. Overall, the lake level fluctuation of Daihai during the early and mid-Holocene was slightly different from the previously published regional records. Possibly, the interaction of the EASM and regional feedback from topography, and hydrology factors might have contributed to the spatial complexity and distinction.